2018
DOI: 10.3390/molecules23040755
|View full text |Cite
|
Sign up to set email alerts
|

Co2 and Co3 Mixed Cluster Secondary Building Unit Approach toward a Three-Dimensional Metal-Organic Framework with Permanent Porosity

Abstract: Large and permanent porosity is the primary concern when designing metal-organic frameworks (MOFs) for specific applications, such as catalysis and drug delivery. In this article, we report a MOF Co11(BTB)6(NO3)4(DEF)2(H2O)14 (1, H3BTB = 1,3,5-tris(4-carboxyphenyl)benzene; DEF = N,N-diethylformamide) via a mixed cluster secondary building unit (SBU) approach. MOF 1 is sustained by a rare combination of a linear trinuclear Co3 and two types of dinuclear Co2 SBUs in a 1:2:2 ratio. These SBUs are bridged by BTB l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 90 publications
0
14
0
Order By: Relevance
“…However, the peak intensities for these two patterns differ considerably. The main reason for this is due to the different orientations of various crystallites in the bulk material. , On the other hand, the pore filling effect is one of the most crucial reasons behind the variation of the diffraction intensity of the experimental (solvated samples) PXRD pattern with reference to that of the theoretical (simulated) pattern. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the peak intensities for these two patterns differ considerably. The main reason for this is due to the different orientations of various crystallites in the bulk material. , On the other hand, the pore filling effect is one of the most crucial reasons behind the variation of the diffraction intensity of the experimental (solvated samples) PXRD pattern with reference to that of the theoretical (simulated) pattern. , …”
Section: Resultsmentioning
confidence: 99%
“…32,33 On the other hand, the pore filling effect is one of the most crucial reasons behind the variation of the diffraction intensity of the experimental (solvated samples) PXRD pattern with reference to that of the theoretical (simulated) pattern. 34,35 3.1.2. N 2 Sorption Isotherm.…”
Section: Photocatalytic Thiocarboxylation Of Styrene Withmentioning
confidence: 99%
“…Nevertheless, the peak intensities for these two patterns are quite different. This is basically happened either due to different orientations of the crystallites in the bulk material or the pore filling effect. , Typically, the intensity variation (either increased or decreased) between the simulated (solvent free samples) and experimental (solvated samples) XRD pattern is described by the pore filling effect. There are also unavoidable TiO 2 peaks, which are formed during the MOF synthesis due to the fast hydrolysis of titanium­(IV) isopropoxide. We have marked these peaks in the PXRD pattern (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The thermally unstable nature of MOF 1 prevented us from studying its surface area via gas adsorption, and our preliminary experiments suggested that MOF 1 exhibits no adsorption of N 2 at 77 K (Supplementary Figure S2), presumably due to the collapse of the 3D framework. The Fourier-transform infrared spectrum (FT-IR) of MOF 1 contained absorptions at 2975 cm −1 , 2930 cm −1 , and 1652 cm −1 corresponding to the-CH 3 , -CH 2 -, and -C=O bonds of te DEF solvate [71,72]. In addition, peaks at 1610 cm −1 , 1536 cm −1 , and 1397 cm −1 were assignable as the asymmetrical and symmetrical stretching vibrations of the carboxylate [66,73].…”
Section: Synthesis and Materials Characterization Of Mofmentioning
confidence: 99%
“…Molecules 2019, 24, x; doi: www.mdpi.com/journal/molecules [71,72]. In addition, peaks at 1610 cm −1 , 1536 cm −1 , and 1397 cm −1 were assignable as the asymmetrical and symmetrical stretching vibrations of the carboxylate [66,73].…”
Section: Molecules 2018 23 X 3 Of 13mentioning
confidence: 99%